2021
DOI: 10.7554/elife.55117
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of stem cell activity in pancreatic cancer expansion by direct lineage tracing with live imaging

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a devastating disease. Although rigorous efforts identified the presence of ‘cancer stem cells (CSCs)’ in PDAC and molecular markers for them, stem cell dynamics in vivo have not been clearly demonstrated. Here we focused on Doublecortin-like kinase 1 (Dclk1), known as a CSC marker of PDAC. Using genetic lineage tracing with a dual-recombinase system and live imaging, we showed that Dclk1+ tumor cells continuously provided progeny cells within pancreatic intraepitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…Doublecortin-like kinase 1 (Dclk1) is a microtubuleassociated protein kinase that was originally known as a tuft cell marker in the intestine [22]. However, Dclk1 is also a marker of TSCs in many cancers, including human CRC [23][24][25][26]. We previously used lineage tracing to demonstrate the stem cell properties of Dclk1-positive (Dclk1 + ) cells in intestinal tumors [27].…”
Section: Introductionmentioning
confidence: 99%
“…Doublecortin-like kinase 1 (Dclk1) is a microtubuleassociated protein kinase that was originally known as a tuft cell marker in the intestine [22]. However, Dclk1 is also a marker of TSCs in many cancers, including human CRC [23][24][25][26]. We previously used lineage tracing to demonstrate the stem cell properties of Dclk1-positive (Dclk1 + ) cells in intestinal tumors [27].…”
Section: Introductionmentioning
confidence: 99%
“…As described earlier, CSC properties can be tested with various assays. Using these assays, many pancreatic CSC markers have been discovered, including, CD133 [14,[114][115][116], CD24 [15,117,118], CD44 [15,117,119,120], ESA [15], Nestin [121], and Dclk1 [90,113,122] or a combination of these markers [14,15] (Figure 3). In addition, it has been shown that migration of CD133 + /CXCR4 + cancer cells is essential in metastasis formation of human pancreatic cancer [14] (Figure 3).…”
Section: Stem Cell Identification and Functionality In Panin Pdac And Metastasismentioning
confidence: 99%
“…Recently, using genetic lineage tracing with a dual‐recombinase system and live imaging, it was shown that doublecortin‐like kinase 1‐positive [Dclk1(+)] tumor cells can continuously produce progeny cells in pancreatic intraepithelial neoplasia, primary and metastatic pancreatic ductal adenocarcinoma (PDAC), and PDAC‐derived spheroids (Sphs) in vivo and in vitro 25 . Furthermore, genes associated with CSC and EMT were enriched in mouse Dclk1(+) and human DCLK1‐high PDAC cells 25 . In the present study, we found that SNAIL2 is highly expressed among the EMT‐TFs including, SNAIL, TWIST, and ZEB family members, in human pancreatic cancer cell lines and patient‐derived Sphs.…”
Section: Introductionmentioning
confidence: 99%